The quest for realism : an assessment of D.C. Maguire's ethical model as a resource in hermeneutical pastoral care and counselling towards moral decision-making for adolescents in the midst of the HIV and AIDS epidemic in South Africa - Janse van Vuren, Johanna Isabella (Stellenbosch : Stellenbosch University, 2017)
Thesis (MTh)--Stellenbosch University, 2017.